Particles as Deictic Phonation - Blankenborg, Ronald (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2019)
This paper focuses on the deictic usage of selected ancient Greek particles, whereby particles primarily represent sounds functioning as symbols. In the study of Greek particles, little words with no stable thesis in prosody, much attention has been given to their auxiliary or nuancing semantic function, sometimes to the effect that a particle was awarded its own independent semantics. This approach, argue, only suits written composition. From a prosodic point of view, the point of view of oral composition and performance, such semantic value is unexpected and often untenable, as rhythmical and intonational clisis resist any adverbial meaning. Usage as particles is the direct result of phonetic reduction, itself the effect of intonational variance. Particles are thus the printed representations of phonemes, of sound. In writing, particles primarily serve prosodic ends. I will argue that the clitic character and the unstable thesis of particles both serve as indicators for intonational deixis.
Keywords: particles; deixis; phonation; aural symbols; prosody of ancient Greek